Perbedaan Model Pembelajaran Modified Free Inquiry (MFI) Berbasis Laboratorium Riil Dengan Virtual Pada Pokok Bahasan Laju Reaksi Terhadap Hasil Belajar Kimia Siswa SMAN 1 Pasangkayu - Eska Perdanawati Kahar Putri; H. Baharuddin Hamzah; Vanny. M. A. Tiwow (Mitra Sains, 2017)
This study aims to determine the differences between MFI learning model based on real and virtual laboratory on the subject of reaction toward the students outcomes of chemical learning at SMAN 1 Pasangkayu. The sample consisted of two classes of grade XI IPA 5 which was 29 people as an experimental class I and grade XI IPA 6 which was 29 people as an experimental class II determined Cluster Random Sampling. Data was collected using test instruments such as achievement test. The research data used statistical analysis t-test (Independent Sample Test) with the prerequisite test was a normality and homogeneity test. The average score of the students outcomes of chemical learning by using MFI model based on real laboratory was 73.01 and the average score of the outcomes of students chemical learning by using MFI model based on virtual laboratory was 80.52. Based on statistical analysis with t-test hypotheses obtained value |tcount| = 3.833 and it was located in the region of rejection of H0 between -2.003 and 2.003. These results indicate that there was a difference between MFI learning model based on real and virtual laboratory on the subject of reaction rate toward the students outcomes of chemical learning at SMAN 1 Pasangkayu.